Crisis Communication and Conflict Resolution (1st edition) - POP-FLANJA, Delia (2021)
Whereas studies on communication in crisis contexts are numerousand substantial (among the most prominent - Benoit, 1995; Witte, 2001, andCoombs, 2006), the current COVID-19 health crisis has caused a disruptionof classical interpretative templates, and a reconsideration of the way inwhich the communication strategies of different actors are applied andinterpreted is necessary.